Endocrine and metabolic factors and the risk of idiopathic pulmonary fibrosis: a Mendelian randomization study - Jiang, Yan; Chen, Rumeng; Xu, Shuling; Ding, Yining; Zhang, Mengling (Frontiers in Endocrinology, 2024)
BackgroundPrevious observational studies have investigated the association between endocrine and metabolic factors and idiopathic pulmonary fibrosis (IPF), yet have produced inconsistent results. Therefore, it is imperative to employ the Mendelian randomization (MR) analysis method to conduct a more comprehensive investigation into the impact of endocrine and metabolic factors on IPF.MethodsThe instrumental variables (IVs) for 53 endocrine and metabolic factors were sourced from publicly accessible genome-wide association study (GWAS) databases, with GWAS summary statistics pertaining to IPF employed as the dependent variables. Causal inference analysis encompassed the utilization of three methods: inverse-variance weighted (IVW), weighted median (WM), and MR-Egger. Sensitivity analysis incorporated the implementation of MR-PRESSO and leave-one-out techniques to identify potential pleiotropy and outliers. The presence of horizontal pleiotropy and heterogeneity was evaluated through the MR-Egger intercept and Cochran’s Q statistic, respectively.ResultsThe IVW method results reveal correlations between 11 traits and IPF. After correcting for multiple comparisons, seven traits remain statistically significant. These factors include: “Weight” (OR= 1.44; 95% CI: 1.16, 1.78; P=8.71×10-4), “Body mass index (BMI)” (OR= 1.35; 95% CI: 1.13, 1.62; P=1×10-3), “Whole body fat mass” (OR= 1.40; 95% CI: 1.14, 1.74; P=1.72×10-3), “Waist circumference (WC)” (OR= 1.54; 95% CI: 1.16, 2.05; P=3.08×10-3), “Trunk fat mass (TFM)” (OR=1.35; 95% CI: 1.10,1.65; P=3.45×10-3), “Body fat percentage (BFP)” (OR= 1.55; 95% CI: 1.15,2.08; P=3.86×10-3), “Apoliprotein B (ApoB)” (OR= 0.78; 95% CI: 0.65,0.93; P=5.47×10-3). Additionally, the sensitivity analysis results confirmed the reliability of the MR results.ConclusionThe present study identified causal relationships between seven traits and IPF. Specifically, ApoB exhibited a negative impact on IPF, while the remaining six factors demonstrated a positive impact. These findings offer novel insights into the underlying etiopathological mechanisms associated with IPF.